STRATEGI GURU PABK (PENDIDIKAN AGAMA DAN BUDI PEKERTI) DALAM MENINGKATKAN RELIGIUSITAS SISWA MELALUI E-LEARNING DI SMA N 1 KARAS, MAGETAN - Siti Nurul Chasanah (Institut Agama Islam Ngawi, 2021)
Abstract Humans are creatures of God who have an essential nature, namely religious creatures (homo religious), where every human being has the nature to understand and accept the values ​​of truth that come from religion. Religion and humans have a natural relationship where religion is integrated in the nature of human creation. This is manifested in noble qualities that need to be developed. Education is one of the strategies in developing human noble qualities and making individuals always remember and get closer to their God (religious). Religion has 5 aspects, Ideological Aspects, Ritualistic Aspects, Experiential Aspects, Intellectual Aspects, Consequential Aspects. These five aspects need to be improved in the concept of e-learning learning which is currently being implemented by the government in line with the COVID-19 pandemic conditions that hit Indonesia. This requires online learning. In the implementation of online learning SMA N 1 Karas has an LMS application and also uses Whatsapp Based on this, the purpose of this research is to find out descriptively based on data in the field how the teacher's strategy is to improve students' religiosity through e-learning. This study used a qualitative method which was analyzed using coding. Based on the data in the field, it is known that the strategies of PABK teachers at SMA N 1 Karas in increasing student religiosity through e-learning are; provide motivation, provide advice, instill religious values ​​in aspects, knowledge, understanding and internalization through learning PABK material delivered by teachers through online learning, implementing and internalizing religious values ​​in daily life through student assignments, preparing teaching aids good and interesting so that students are able to understand the concept of religiosity, the teacher prays for students to always be istiqamah and get ridho from Allah. Keyword: PABK Teacher, Student Religiosity